Plant Growth Promoting Rhizobacteria and Plants’ Improvement- A Mini-Review - Siyar, Saira; Inayat, Naila; Hussain, Fida (PSM Biological Research, 2018)
The soil is a rich compendium of diverse organisms which have multifaceted roles in the ecological dynamics. The diversity and functional activity of the soil-borne organisms depend on the soil structure and the types of nutrients available there. From the perspectives of plants growth and development, these organisms may be beneficial, harmful or neutral. Among the organisms, plant growth promoting rhizobacteria (PGPR) constitute a significant and ecologically important portion which directly or indirectly corresponds to the growth improvement of plants. PGPR are of diverse types. Some of these bacteria are found in symbiotic association with hosts while others remain free living. They are efficiently involved in nitrogen fixation, phosphate, and iron solubilization, mitigation of heavy metals and other pollutants, antagonism with phytopathogens, and the production of growth promoting molecules. The net consequences of PGPR activities are growth stimulation of plants. Here we review the importance of PGPR and their role in growth improvement of cultivated crops.